How Long Do We Need to Treat an Invasive Mold Disease in Hematology Patients? Factors Influencing Duration of Therapy and Future Questions. (14th March 2020) - Fernández-Cruz, Ana; Lewis, Russell E; Kontoyiannis, Dimitrios P
Abstract: Treatment duration for invasive mold disease (IMD) in patients with hematological malignancy is not standardized and is a challenging subject in antifungal stewardship. Concerns for IMD relapse during subsequent reinduction or consolidation chemotherapy or graft versus host disease treatment in hematopoietic stem cell transplant recipients often results in prolonged or indefinite antifungal treatment. There are no validated criteria that predict when it is safe to stop antifungals. Decisions are individualized and depend on the offending fungus, site and extent of IMD, comorbidities, hematologic disease prognosis, and future plans for chemotherapy or transplantation. Recent studies suggest that FDG-PET/CT could help discriminate between active and residual fungal lesions to support decisions for safely stopping antifungals. Validation of noninvasive biomarkers for monitoring treatment response, tests for quantifying the "net state of immunosuppression, " and genetic polymorphisms associated with poor fungal immunity could lead to a personalized assessment for the continued need for antifungal therapy. Abstract : The duration of antifungal therapy for invasive mold disease needs to be individualized according to improvement in or resolution of attributable signs and symptoms, follow-up radiology and fungal biomarkers, and future plans for treatment of underlying hematologic malignancy.